Investigating the Challenges of Studying Science in English as a Medium of Instruction: Foundation Year Students’ Perceptions at the University of Jeddah - Alasmari, Nasser (International Journal of Learning, Teaching and Educational Research, 2023)
Undeniably, there has been a growing demand for the acquisition of the English language in recent decades. Despite the serious efforts made to intensively use this language in Saudi educational settings, its implementation as a medium of instruction (MOI) still poses challenges and obstacles to students, especially those specializing in scientific branches. The incorporation of English as a medium of instruction (EMI) at the tertiary level is not a new topic to be explored. However, revisiting such aspect of research is highly recommended. This is particularly true in unexplored areas, as is the case in the current research, which was conducted at the University of Jeddah. The study aimed to investigate the difficulties and challenges of studying scientific subjects in English as MOI as perceived by Foundation Year Saudi students. A sample of 113 newly admitted students participated in this study. Two main research instruments were qualitatively used for data collection, namely a questionnaire and semi-structured interview. The results indicate students’ recognition of the importance of the English language. Results also indicate the existence of language-related difficulties, such as students’ inadequate English proficiency, and other kinds of challenges to be major barriers impeding the effective incorporation of EMI. Such obstacles involve teacher competency level and insufficient course materials in addition to students’ lack of motivation and interest. Some recommendations on how to overcome such obstacles are included in this paper.